Treatment of a femoral fracture with a titanium locking compression plate distal femur (LCP‐DF) in a young donkey. (24th May 2013) - Bumbacher, S.; Bryner, M. F.; Fürst, A. E.; Del Chicca, F.; Ringer, S. K.; Jackson, M. A.
<x xml:space="preserve">Abstract</x> See also Clinical Commentary by Barr